The gap between parental knowledge and children practice of myopia control and challenge under COVID-19: a web-based survey in China - Yuan, Hao; Lv, Huibin; Li, Xuemin (Frontiers in Public Health, 2024)
Objective: To evaluate parental knowledge of myopia control, investigate its association with children's practice and refractive status.Methods: In this web-based survey, a self-administered questionnaire was made online available during the COVID-19 outbreak between February 1 th , 2022 and August 31 th , 2022 in China.Participants were recruited via social media by convenience and snowball sampling. Parents of both sexes whose children aged between 3 and 18 were eligible. The overall questionnaire was composed of four categories: demographic information, parental knowledge of myopia, children's myopia-related behaviors and children's refractive status. SPSS version 18.0 was applied to perform the statistics analysis and p<0.05 was considered to be statistically significant.Results: A total of 423 eligible families were included in our online survey. The average age of children was 11.37 ± 2.83y (male 46.1%; female 53.9%), with a myopia incidence of 83.9% (355/423). Both children's age (OR=-0.6; 95%CI=-1.12 to -0.07; p=0.026) and family income (OR=2.60; 95%CI=1.13 to 4.07; p=0.001) had independently significant impacts on parental knowledge. Unexpectedly, parental knowledge was negatively correlated with children's onset age of myopia (p=0.002, r=-0.165) and positively correlated with spectacles wearing (p=0.014, r=0.131), and no correlation was found between parental knowledge and the occurrence of children myopia, current diopter, annual myopia progression and the diopter of the first glasses (all p ＞ 0.05). We found discordance phenomenon between parents' knowledge and children's behaviors, with parental knowledge being irrelevant to children's sleeping time (p=0.159, r=0.069), the frequency of lying reading (p=0.462, r=-0.036) and keeping nutrition diet (p=0.142, r=0.072), and positively correlated with daily homework time (p=0.012, r=0.123). The ideal interaction mode that establishing positive impact between parental knowledge and children practice has not been reached in China, which might be the result of insufficient parents' cognition and discordance phenomenon between parental knowledge and children's behaviors.